SOCIO-PHILOSOPHICAL FACTORS OF IMPLEMENTATION OF THE IDEA OF NATIONAL DEVELOPMENT (Scientific journal of the Fergana State University, 2023)
The article explores the essence and integrative function of the National idea, the socio-spiritual, political and historical foundations of the idea of ensuring the ideological unity of the people at a new stage of development of Uzbekistan, its implementation on the basis of the idea of national rise.